Анализ направлений исследований особенностей приграничного региона – Республики Карелии - Kovshov A. S. (Priority directions of science and education development, 2017)
a brief analysis of the directions of research of the features of the economic, industrial and social sphere of the northern border region - the Republic of Karelia, is given.
Keywords: Республика Карелия; регионы России; the Republic of Karelia; features of the border region; regions of Russia; особенности приграничного региона